Further treatment of palm oil mill effluent using physical chemical treatment using various coagulants and recycled iron sludge / Chooi Wai Fun, M. Rizwan UI Haq and Shamsul Rahman M. Kutty - Chooi, Wai Fun; UI Haq, M. Rizwan; M. Kutty, Shamsul Rahman (2006)
Palm Oil Mill Effluent (POME) is known to cause serious environmental hazards due to its high biological and chemical oxygen demand if disposed without treatment. Moreover, the processing of palm fruit causes POME to have fibre and husk causing high level of total suspended solids (TSS) and turbidity. This work focused on the reduction of chemical oxygen demand (COD), turbidity and TSS based on physical-chemical treatment. Effluent samples were taken from a near-by palm oil mill. Aluminium sulphate and ferric chloride were utilized as coagulants. The experimental results showed that pH decreased with coagulant dosage due to acid production. The optimum dosage for alum was found to be 6000mg/L at pH range 6 - 6.5. The results had shown 99% reduction in turbidity, 91.5% reduction COD and 60% reduction for TSS. Whereas, the optimum dosage for ferric chloride was found to be 2600 mg/L with pH 6 giving 99% reduction in turbidity, 95% and 97% reduction in COD and TSS, respectively Ferric chloride was found to be the more effective coagulant. Further studies were conducted using recycled iron sludge (RIS) from Kelantan water treatment plant and it was revealed that RIS had produced comparable results with ferric chloride and alum showing 86% reduction in COD with the optimal dosage of 800 mg/l which was less than the dosage required for alum and ferric chloride.